Effectiveness of influenza vaccination during pregnancy to prevent severe infection in children under 6 months of age, Spain, 2017–2019. Issue 52 (14th December 2020) - Mazagatos, Clara; Godoy, Pere; Muñoz Almagro, Carmen; Pozo, Francisco; Larrauri, A; ,; Gallardo García, Virtudes; López Hernández, Begoña; García, Miriam; Huerta González, Ismael; Giménez Duran, Jaume; Falcón García, Isabel; et al.
Abstract: Introduction: Influenza vaccination is recommended to pregnant women in Spain to reduce the risk of influenza-related complications. Influenza related hospitalizations pose a significant disease burden in children every year. Although children below 6 months are too young to be vaccinated, they can receive protection against influenza through vaccination of their mothers during pregnancy. We estimated the effectiveness of maternal influenza vaccination to prevent influenza hospitalizations in infants under 6 months of age. Methods: This is a retrospective pilot study, using data from the Severe Hospitalized Confirmed Influenza Cases (SHCIC) surveillance system in seasons 2017/18 and 2018/19 in Spain. Maternal vaccination status during pregnancy was collected for cases in children 6 months and younger hospitalized with confirmed influenza infection. Influenza vaccine effectiveness was estimated using the screening method, by comparing the proportion of children with vaccinated mothers during pregnancy (proportion of cases vaccinated, PCV), with the vaccination coverage among pregnant women in Spain (proportion of population vaccinated, PPV). Results: For all the study period, the PCV was 17% and the PPV was 35%. Influenza vaccination in mothers during pregnancy prevented influenza confirmed hospitalizations in infants aged 6 months and younger with a 61% (95%CI: 27–79%) effectiveness. Conclusions: In line with evidence from other countries, influenza vaccination during pregnancy protects infants up to 6 months of age from influenza hospitalizations in Spain. These results support current recommendations of influenza vaccination in pregnant women, and more studies are needed in Spain to confirm the double protection of maternal vaccination in mothers and infants.